Робастное управление главными приводами прокатных станов - Казурова, Алина Евгеньевна (НТУ "ХПИ", 2013)
The rolling mills main drivers control with synchronous motors, which are presented as a two-mass and three-mass electromechanical systems, is considered. The object work is accompanied by a nonlinear friction. Motors speeds are only measured. For these systems the robust combined regulators with uncertainties observers are designed. The availability of the control algorithms is confirmed by numerical simulation.
Keywords: прокатное производство; синхронные двигатели; нелинейное трение; скорость вращения двигателей; комбинированные регуляторы; наблюдатели неопределенности